1991
DOI: 10.1093/clinchem/37.11.1950
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of lipoprotein(a) to variables of coagulation and fibrinolysis in a healthy population

Abstract: In the Prospective Cardiovascular Münster (PROCAM) study, serum lipoprotein(a) [Lp(a)] and its relationship to pro- and anticoagulatory as well as fibrinolytic indices were determined in a large group of employees: 864 men (m) and 373 women (f), ages 16-65 years. Univariate statistical analysis showed Lp(a) concentration to be associated with fibrinogen concentrations in both sexes (m: r = 0.08, P less than 0.05; f: r = 0.20, P less than 0.001), but not with euglobulin fibrinolysis activity, tissue-type plasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(38 citation statements)
references
References 14 publications
2
33
2
1
Order By: Relevance
“…A higher proportion of Pakistani women (40%) had Lp(a) levels greater than 300 mg L −1 , the threshold at which increased risk of CHD is believed to occur. Several studies have suggested an increase in Lp(a) levels after menopause [9,29]. However, in this study, age did not correlate with Lp(a) levels in South Asian women and therefore the differences cannot be explained by age-dependent hormonal changes.…”
Section: Males Females Males Femalescontrasting
confidence: 85%
See 1 more Smart Citation
“…A higher proportion of Pakistani women (40%) had Lp(a) levels greater than 300 mg L −1 , the threshold at which increased risk of CHD is believed to occur. Several studies have suggested an increase in Lp(a) levels after menopause [9,29]. However, in this study, age did not correlate with Lp(a) levels in South Asian women and therefore the differences cannot be explained by age-dependent hormonal changes.…”
Section: Males Females Males Femalescontrasting
confidence: 85%
“…A positive association between Lp(a) and fibrinogen is well established in Europeans [9,29] even though there is no obvious explanation for this relationship. We found a stronger association between Lp(a) and fibrinogen in women than men, which is in agreement with the data reported by Heinrich et al [29]. This relationship was also seen in South Asians (statistically significant in men).…”
Section: Males Females Males Femalesmentioning
confidence: 99%
“…There are no major differences in Lp(a) levels between men and women. However, Lp(a) levels are higher in postmenopausal compared with premenopausal women [139]. In line with this, meta-analyses of women using hormone-replacement therapy with various agents demonstrated an average decrease in Lp(a) of about 25% with no major difference between oral and transdermal agents [140,141].…”
Section: Sex Hormonesmentioning
confidence: 77%
“…Multivariate regression analysis confirmed the negative correlation between the concentrations of Lp(a) and TG (r = -0.31; P < 0.001) as well as the positive correlation with HDL-cholesterol ( Table 2). These relationships were not observed in 1237 controls from the Prospective Cardiovascular Munster (PROCAM) Study [19,20].…”
Section: Resultsmentioning
confidence: 92%